The association of a paraprofessional home visiting intervention with lower child maltreatment rates in First Nation families in Canada: A population-based retrospective cohort study. (January 2020) - Chartier, Mariette; Enns, Jennifer E; Nickel, Nathan C; Campbell, Rhonda; Phillips-Beck, Wanda; Sarkar, Joykrishna; Lee, Janelle Boram; Burland, Elaine; Chateau, Dan; Katz, Alan; Santos, Robert; Brownell, Marni
Highlights: Families First Home Visiting serves families facing multiple parenting challenges. The program is available to First Nation families living off-reserve in Manitoba. Enrolled families are less likely to have their children taken into care. Keeping families together is a key message of the Truth & Reconciliation Commission. Enhanced efforts to enroll First Nation families in the program may be warranted. Abstract: Background: The Families First Home Visiting (FFHV) program aims to enhance parenting skills and strengthen relationships between parents and their children. Previous research found FFHV to be effective at decreasing child maltreatment in the general population of Manitoba, but whether it is beneficial specifically for First Nation families has not yet been investigated. Methods: De-identified home visiting program data from 4010 First Nation families with children born 2003–2009 were linked to population-based administrative data housed at the Manitoba Centre for Health Policy. We applied inverse probability of treatment weights to adjust for confounders related to enrollment in FFHV, and then compared rates of children taken into care of child welfare, maltreatment-related hospitalization, and children witnessing or being a victim of a crime in FFHV-enrolled families to rates in families eligible for but not enrolled in FFHV. Results: FFHV enrollment was associated with lower rates of children being taken into care before the age of 1 (adjusted Risk Ratio [aRR] 0.687; 95% Confidence Interval [CI] 0.576–0.819) and age 2 (aRR 0.763; 95% CI 0.611–0.881), lower rates of hospitalization for maltreatment-related injuries by age 3 (aRR 0.429; 95% CI 0.187–0.983), and lower rates of children witnessing or being a victim of a crime (aRR 0.591; 95% CI 0.385–0.907). Conclusions: Families enrolled in FFHV had lower rates of maltreatment-related indicators compared to families eligible for but not enrolled in the program. Strategies for increasing enrollment through partnerships with First Nation organizations are recommended.